Influence of carrier gas flow rate on carbon nanotubes growth by TCVD with Cu catalyst - S.A. Khorrami; R. Lotfi (Journal of Saudi Chemical Society)
Carbon nanotubes (CNTs) were grown on copper catalyst by thermal chemical vapor deposition (TCVD) using H2 and N2 as carrier gases. CNTs with different morphologies were observed using different carrier gas flow rates. The influence of carrier gas flow rates on the structure of carbon nanotubes was compared. Catalyst nanolayer was sputtered on mirror polished silicon wafers. The catalyst film thickness was determined by using the Rutherford Back Scattering (RBS) technique. Ethanol as carbon source has been used. The surface morphology and nanostructure were studied by Scanning Electron Microscopy (SEM), Raman Spectroscopy, Tunneling Electron Microscopy (TEM) and Atomic Force Microscopy (AFM). Results indicated that the amounts of deposited carbon decrease with increasing flow rates. These results showed that CNTs’ length decreased with increasing flow rates. Results suggest that Cu nanolayer is suitable as catalyst due to the fact that CNTs are monotonous.